Direct tactile stimulation of dorsal occipito-temporal cortex in a visual agnosic - Allen, Harriet A.; Humphreys, Glyn W. (Elsevier (Cell Press), 2009)
The human occipito-temporal cortex is preferentially activated by images of objects as opposed to scrambled images [1]. Touching objects (versus textures) also activates this region [2–10]. We used neuropsychological fMRI to probe whether dorsal regions of the lateral occipital cortex (LO) are activated in tactile recognition without mediation through visual recognition. We tested a patient (HJA) with visual agnosia due to bilateral lesions of the ventral occipito-temporal cortex but spared dorsal LO. HJA's recognition of visual objects was impaired [11, 12]. Nevertheless, his tactile recognition was preserved. We measured brain activity while participants viewed and touched objects and textures. There was overlapping activity in regions including LO and cerebellum for both stimuli for control participants, including new regions not before considered bimodal. For HJA, there were overlapping regions in the intact dorsal LO. Within a subset of the regions found in control participants, HJA showed activity only for tactile objects, suggesting that these regions are specifically involved in successful multimodal recognition. Activation of dorsal LO by tactile input is not secondary to visual recognition but can operate directly through tactile input.